2019
DOI: 10.3389/fgene.2018.00721
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Network and Prognostic Effect Investigation of PIP4K2A in Leukemia and Solid Cancers

Abstract: Germline variants of PIP4K2A impact susceptibility of acute lymphoblastic leukemia (ALL) through inducing its overexpression. Although limited reports suggested the oncogenic role of PIP4K2A in cancers, regulatory network and prognostic effect of this gene remains poorly understood in tumorigenesis and leukemogenesis. In this study, we conducted genome-wide gene expression association analyses in pediatric B-ALL cohorts to discover expression associated genes and pathways, which is followed by the bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Further, we have shown elevated expression of the PI5P4Ks in breast tumors compared to normal breast tissue (Emerling et al, 2013) and other studies have shown the impact of the kinases in breast cancer (Luoh et al, 2004;Keune et al, 2013). Similarly, PI5P4Ks have been demonstrated to be upregulated in several cancer subtypes, including glioblastomas, AML, and sarcomas (Fiume et al, 2015;Jude et al, 2015;Zhang et al, 2018;Lima et al, 2019;Shin et al, 2019;Ravi et al, 2021). Moreover, we recently illustrated the requirement of the PI5P4Ks for not only the establishment of sarcoma tumors but also in maintaining them, possibly through their role in regulating peroxisomemitochondrial interplay (Ravi et al, 2021).…”
Section: Health and Disease: Pi5p4ks Emerge As Exciting Targetssupporting
confidence: 63%
“…Further, we have shown elevated expression of the PI5P4Ks in breast tumors compared to normal breast tissue (Emerling et al, 2013) and other studies have shown the impact of the kinases in breast cancer (Luoh et al, 2004;Keune et al, 2013). Similarly, PI5P4Ks have been demonstrated to be upregulated in several cancer subtypes, including glioblastomas, AML, and sarcomas (Fiume et al, 2015;Jude et al, 2015;Zhang et al, 2018;Lima et al, 2019;Shin et al, 2019;Ravi et al, 2021). Moreover, we recently illustrated the requirement of the PI5P4Ks for not only the establishment of sarcoma tumors but also in maintaining them, possibly through their role in regulating peroxisomemitochondrial interplay (Ravi et al, 2021).…”
Section: Health and Disease: Pi5p4ks Emerge As Exciting Targetssupporting
confidence: 63%
“…High expression of not only PI5P4Ka but also of PI5P4Kc was found to be associated with unfavorable clinical outcomes for AML patients [43]. Genome-wide association studies have also identified several single nucleotide polymorphisms (SNPs) in the PIP4K2Α locus that have been associated with a genetic predisposition in ALL [48][49][50]; however, the contribution of the SNPs to PIP4K2A expression or the functional involvement of PI5P4Ka to the leukemogenesis of ALL is still unexplored. Nevertheless, targeting PI5P4Ks in acute leukemias could be a promising treatment either by itself or as a combination therapy [45].…”
Section: Acute Leukemiasmentioning
confidence: 99%
“…High transcript levels of PIP4K2A and PIP4K2C were predictive of poor prognosis in AML patients [22,23]. Furthermore, SNPs in the regulatory region of the PIP4K2A gene were associated with increased mRNA levels and susceptibility to ALL development [19,20].…”
Section: Discussionmentioning
confidence: 95%
“…; https://doi.org/10.1101/2022.08. 20.504641 doi: bioRxiv preprint 4 PIP4K2C transcript levels were associated with adverse cytogenetic risk and poor clinical outcome [22,23]. THZ-P1-2 is the prototype of a new class of drugs that acts as a selective pan-inhibitor of PIP4K2s.…”
Section: Introductionmentioning
confidence: 99%